Baumol's cost disease in acute versus long-term care: Do the differences loom large? - Kaan Celebi; Jochen Hartwig; Anna Pauliina Sandqvist (International Journal of Health Economics and Management, 2025)
Baumol's (Am Econ Rev 57: 415–426, 1967) model of 'unbalanced growth' yields a supply-side explanation for the 'cost explosion' in health care. Applying a testing strategy suggested by Hartwig (J Health Econ 27: 603–623, 2008), a sprawling literature affirms that the 'Baumol effect' has both a statistically and economically significant impact on health care expenditure growth. Skeptics maintain, however, that the proliferation of hi-tech medicine in acute care is clearly at odds with the assumption underlying Baumol's model that productivity-enhancing machinery and equipment is only installed in the 'progressive' (i.e. manufacturing) sector of the economy. They argue that Baumol's cost disease may affect long-term care, but not acute care. Our aim in this paper is to test whether Baumol's cost disease affects long-term care and acute care differently. Our testing strategy consists in combining Extreme Bounds Analysis (EBA) with an outlier-robust MM estimator. Using panel data for 23 OECD countries, our results provide robust and statistically significant evidence that expenditures on both acute care and long-term care are driven by Baumol's cost disease, even though the effect on long-term care expenditures is more pronounced.
Keywords: C12; C23; I10; 330; Health care expenditure; Baumol's cost disease; Extreme Bounds Analysis; MM estimator; OECD panel